European guideline and expert statements on the management of narcolepsy in adults and children - Bassetti, Claudio L A; Kallweit, Ulf; Vignatelli, Luca; Plazzi, Giuseppe; Lecendreux, Michel; Baldin, Elisa; Dolenc-Groselj, Leja; Jennum, Poul; Khatami, Ramin; Manconi, Mauro; Mayer, Geert; Partinen, Markku; et al. (European journal of neurology, 2021)
BACKGROUND AND AIM: Narcolepsy is an uncommon hypothalamic disorder of presumed autoimmune origin that usually requires lifelong treatment. This paper aims to provide evidence-based guidelines for the management of narcolepsy in both adults and children. METHODS: The European Academy of Neurology (EAN), European Sleep Research Society (ESRS) and European Narcolepsy Network (EU-NN) nominated a task force of 18 narcolepsy specialists. According to the EAN recommendations, 10 relevant clinical questions were formulated in PICO format. Following a systematic review of the literature (performed in Fall 2018 and updated in July 2020) recommendations were developed according to the GRADE approach. RESULTS: A total of 10,247 references were evaluated, 308 studies were assessed and 155 finally included. The main recommendations can be summarized as follows: (i) excessive daytime sleepiness in adults-scheduled naps, modafinil, pitolisant, sodium oxybate (SXB), solriamfetol (all strong), methylphenidate, amphetamine derivates (both weak); (ii) cataplexy in adults-SXB, venlafaxine, clomipramine (all strong) and pitolisant (weak); (iii) excessive daytime sleepiness in children-scheduled naps, SXB (both strong), modafinil, methylphenidate, pitolisant, amphetamine derivates (all weak); (iv) cataplexy in children-SXB (strong), antidepressants (weak). Treatment choices should be tailored to each patient's symptoms, comorbidities, tolerance and risk of potential drug interactions. CONCLUSION: The management of narcolepsy involves non-pharmacological and pharmacological approaches with an increasing number of symptomatic treatment options for adults and children that have been studied in some detail.
Keywords: dospělí; Narcolepsy; Modafinil; modafinil; Humans; Child; lidé; kataplexie; Sodium Oxybate; spánek; dítě; oxybát sodný; Cataplexy; Adult; Sleep; narkolepsie